A comparative study of the structural and functional properties of isolated hemp seed (Cannabis sativa L.) albumin and globulin fractions. (January 2015) - Malomo, Sunday A.; Aluko, Rotimi E.
Abstract: The aim of this work was to determine the structural and functional characteristics of two major hemp seed proteins, the water-soluble albumin (ALB) and the salt-soluble globulin (GLB). The 0.5 M NaCl extract of hemp seed protein flour was dialyzed against water to obtain the two fractions: ALB in the water phase and GLB in the insoluble precipitate. The protein fractions were subjected to structural (gel electrophoresis, intrinsic fluorescence and circular dichroism) and functional (protein solubility, foaming, and emulsion) tests. Amino acid composition data showed the presence of higher contents of aromatic and hydrophobic residues in GLB. Gel electrophoresis indicated that the ALB has less disulfide bonds and hence a more open (flexible) structure; this was confirmed by the intrinsic fluorescence and circular dichroism data showing greater exposure of tyrosine residues when compared to GLB. ALB had significantly ( p < 0.05) higher protein solubility and foaming capacity than the GLB at all the pH or sample concentration values but emulsion forming ability was similar for both protein fractions. Differences in emulsion stability were observed mostly at 10 mg/mL sample concentration; these differences were minimized at 25 mg/mL and eliminated at 50 mg/mL. We conclude that the ALB fraction will serve as excellent ingredient for food foam formulation while the GLB may be slightly more useful than the ALB in the formulation of food emulsions. Graphical abstract: Highlights: At pH 3.0–9.0 range, hemp seed albumin was more soluble than the globulin. Intrinsic fluorescence showed albumin with more open structure than globulin. Aromatic and hydrophobic amino acids were higher in the globulin than albumin. Foaming capacity was higher for albumin than the globulin. Emulsion oil droplet size was small (<1 μm) but similar for both albumin and globulin.